Optimization of culture medium and bioformulation of rhizobial actinomycetes to enhance soybean plant growth - UMI FATMAWATI; MEFTA RIZKI QURRATA’AINI; NOVIAN WILDAN ROSYIDI; DEWI PUSPITA SARI; SLAMET SANTOSA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fatmawati U, Qurrata’aini MR, Rosyidi NW, Sari DP, Santosa S. 2023. Optimization of culture medium and bioformulation of rhizobial actinomycetes to enhance soybean plant growth. Biodiversitas 24: 2912-2918. Actinomycetes are a group of Gram-positive bacteria that are well-known for having plant growth-promoting activity. In an earlier study, Streptomyces sp. strain ASR 58 and Streptomyces sp. strain ASR 67, isolated from soybean rhizosphere, were found to be capable of producing Indole-Acetic Acid (IAA), dissolving phosphate, and stimulating soybean growth. Optimization of culture media and selection of carrier materials for formulation are necessary to maintain actinomycetes' cell viability and plant growth property stability. This study aimed to evaluate several culture media, determine the optimal carrier materials in actinomycetes formulation, and evaluate the effect of actinomycete bioformulation on the soybean plant growth in planta. The sugar potato broth medium was the best in increasing the cell biomass of ASR 67 and co-culture of ASR 58 and ASR 67 compared to other mediums (skim molasses and rice bran broth). The viability of ASR 58 cell (5.3 x 107 CFU/mL), ASR 67 (3.8 x 107 CFU/mL), and its combination of both (4.3 x 107 CFU/mL) was best maintained in talc powder carrier during 10 weeks of storage as revealed by the number of viable cells decreases. Applying ASR 58 and ASR 67 co-culture on talc powder formula enhanced soybean plant biomass four weeks after planting, including plant height, the number of leaves, and root dry weight.